Behaviour of a strip footing adjacent to the existing supported excavation - Gör, Mesut; Taher, Nichirvan Ramadhan; Aksoy, Suha (My University, 2023)
This study investigates the results of the numerical analysis on effect of existing supported excavation on ultimate bearing capacity (qult) of strip footing adjacent to supported excavation in sandy soil. The influence of distance (L) between the foundation and the supported excavation was studied as well as the effect of the excavation depth (He). For this purpose, on a full-scale model, a series of numerical calculations were carried out to determine how (L) and (He) affected the behavior of strip foundation. Based on finite element approach, the computer software Plaxis 2D code was utilized. Non-linear hardening soil model, a sophisticated elastoplastic stressstrain constitutive soil model, was used to characterize sandy soil. Based on Mindlin's beam theory, the strip footing and sheet pile wall were identified as elastic beam components with significant flexural rigidity (EI) and axial stiffness (EA). The sheet pile was installed at three different distances (L) away from the face of the strip foundation 1B, 1.5B and 2B, where B is the width of foundation. For each distance, three different excavations (He) were used with dimensions 1B, 1.5B and 2B. The numerical outcomes show that the ultimate bearing capacity (qult) of shallow foundation is decreased when distance between strip foundation and supported excavation is decreased, and vice versa. Additionally, (qult) is reduced as the depth of excavation behind sheet pile wall is increased, and vice versa.
Keywords: Sheet pile; Finite element methods; Supported excavation; Strip foundation; Excavation depth